2015
DOI: 10.1016/j.pharep.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simvastatin on malondialdehyde level and esterase activity in plasma and tissue of normolipidemic rats

Abstract: SIMV significantly decreased PON1 activity and MDA levels and increased BuChE activity. We suggest that the decrease of MDA levels is a beneficial therapeutic effect of SIMV, for example in cardiovascular disorders, while the increase of BuChE activity, especially in brain, may be a potential adverse effect in patients with Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…To date, many hypolipidemic drugs have been used to control serum cholesterol levels and to prevent hyperlipidemia. Among these drugs, statins are widely used to retard the atherosclerosis in patients with hyperlipidemia (Macan et al, 2015). In fact, these drugs have also been reported to present anti-inflammatory, anticancer, antioxidant and immunomodulatory effects (Chen et al, 2018;Rizvi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To date, many hypolipidemic drugs have been used to control serum cholesterol levels and to prevent hyperlipidemia. Among these drugs, statins are widely used to retard the atherosclerosis in patients with hyperlipidemia (Macan et al, 2015). In fact, these drugs have also been reported to present anti-inflammatory, anticancer, antioxidant and immunomodulatory effects (Chen et al, 2018;Rizvi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conveyed that the metabolism of SV is complex and involves the oxidative biotransformation mainly by CYP3A [41,42]. Studies also indicated that SV can be hydrolyzed to SVA by esterases, paraoxonases or through chemical approaches [43,44]. UGTs, especially UGT1A1 and UGT1A3, were also found as SV metabolizing proteins which catalyze the formation of glucuronide conjugates of SVA and its reversible conversion to SV [45].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo non-clinical investigations have evidenced that statins either decrease or have no effect on AChE and BuChE activity (16,17). Our recent study, however, has shown that simvastatin significantly increases plasma and liver BuChE activity in normolipidemic rats (18). Fibrates have also been shown to increase BuChE activity in non-clinical studies (19,20).…”
mentioning
confidence: 89%